3D graphene-Fe3O4-polyaniline, a novel ternary composite for supercapacitor electrodes with improved electrochemical properties. (September 2017) - Mezgebe, Mebrahtu Melake; Yan, Zhengquan; Wei, Gang; Gong, Shuishui; Zhang, Fayin; Guang, Shanyi; Xu, Hongyao
Abstract: To develop a promising electrode candidate for high-performance supercapacitors, a novel 3D ternary composite, graphene-Fe3 O4 -polyaniline (rGO/Fe3 O4 /PANI), was designed and developed via in-situ hydrothermal polymerization methods. After its structure and performances were characterized by powder X-ray diffraction, scanning electron microscope, high-resolution transmission electron microscopy, Fourier transform infrared spectroscopy, Raman spectroscopy, ultraviolet-visible absorption spectroscopy and Brunauer-Emmett-Teller (BET), the electrochemical enhanced mechanisms for supercapacitor electrodes were explored carefully. By virtue of the excellent synergistic effect among Fe3 O4, PANI and rGO, the electrochemical properties of rGO/Fe3 O4 /PANI-based electrode for supercapacitor were improved greatly. The specific capacitance increased from 299.1 Fg −1 for PANI, to 371.1 Fg −1 for rGO/PANI and further to 486.5 Fg −1 for rGO/Fe3 O4 /PANI. Importantly, even after 2000 cycles, the retention ratio could still keep 52.1% for rGO/Fe3 O4 /PANI comparing with 38.9% for PANI. Graphical abstract: Highlights: The 3D ternary composite (rGO/Fe3 O4 /PANI) was constructed via in-situ hydrothermal polymerization methods. Its electrochemical activities was improved by synergistic effect between components. Specific capacitance was enhanced greatly from PANI (299.1 Fg −1 ) to rGO/Fe3 O4 /PANI (486.5 Fg −1 ). rGO/Fe3 O4 /PANI electrode showed improved retention ratio compared to pure PANI.